Response of microbial communities in the phyllosphere ecosystem of tobacco exposed to the broad-spectrum copper hydroxide - Feng, Ruichao; Wang, Hancheng; Liu, Tingting; Wang, Feng; Cai, Liuti; Chen, Xingjiang; Zhang, Songbai (Frontiers in Microbiology, 2023)
Copper hydroxide is a broad-spectrum copper fungicide, which is often used to control crop fungal and bacterial diseases. In addition to controlling targeted pathogens, copper hydroxide may also affect other non-targeted microorganisms in the phyllosphere ecosystem. At four time points (before spraying, and 5, 10 and 15 days after fungicide application), the response of diseased and healthy tobacco phyllosphere microorganisms to copper hydroxide stress was studied by using Illumina high-throughput sequencing technology, and Biolog tools. The results showed that the microbiome communities of the healthy group were more affected than the disease group, and the fungal community was more sensitive than the bacterial community. The most common genera in the disease group were Alternaria, Boeremia, Cladosporium, Pantoea, Ralstonia, Pseudomonas, and Sphingomonas; while in the healthy group, these were Alternaria, Cladosporium, Symmetrospora, Ralstonia, and Pantoea. After spraying, the alpha diversity of the fungal community decreased at 5 days for both healthy and diseased groups, and then showed an increasing trend, with a significant increase at 15 days for the healthy group. The alpha diversity of bacterial community in healthy and diseased groups increased at 15 days, and the healthy group had a significant difference. The relative abundance of Alternaria and Cladosporium decreased while that of Boeremia, Stagonosporopsis, Symmetrospora, Epicoccum and Phoma increased in the fungal communities of healthy and diseased leaves. The relative abundance of Pantoea decreased first and then increased, while that of Ralstonia, Pseudomonas and Sphingomonas increased first and then decreased in the bacterial communities of healthy and diseased leaves.Alternaria and Cladosporium, it also resulted in the decrease of beneficial bacteria such as Actinomycetes and Pantoea, and the increase of potential pathogens such as Boeremia and Stagonosporopsis. After treatment with copper hydroxide, the metabolic capacity of the diseased group improved, while that of the healthy group was significantly suppressed, with a gradual recovery of metabolic activity as the application time extended. The results revealed changes in microbial community composition and metabolic function of healthy and diseased tobacco under copper hydroxide stress, providing a theoretical basis for future studies on microecological protection of phyllosphere.